PERAN LINGKUNGAN PESANTREN TERHADAP TATANAN BAHASA HONORIFIK SANTRI DI SMP A. WAHID HASYIM TEBUIRENG - Hablana Milladunkah Rohmah; Raras Hafidha Sari; Claudia Zahrani Susilo; Syamrotul Musfiroh (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2026)
This study aims to determine the influence of the Islamic boarding school environment on the honorific language structure of students at SMP A. Wahid Hasyim Tebuireng. The focus of the study is directed at how the daily life and culture of the Islamic boarding school shape the language habits of students, especially in the use of speech forms that show respect (honorifics). In this context, honorifics are understood not only as greetings, but also as part of the grammar of politeness and social hierarchy that reflect the values ​​of Islamic boarding school ethics. This study uses a descriptive qualitative approach with a naturalistic observation method, namely the researcher directly observes the language habits of students in daily activities at school and the Islamic boarding school environment. Data are collected through field notes, then analyzed and conclusions are drawn. The results of the study indicate that the Islamic boarding school environment has a strong influence on the honorific language structure of students. In daily interactions, students are accustomed to using polite and respectful language forms, such as the greetings "Ustaz", "Ustazah", "Panjenengan", as well as polite forms of speech such as "nggih", "monggo", and "nuwun sewu". The use of these forms not only reflects linguistic habits but also reflects the internalization of the values ​​of ta'dzim (respect for teachers) and tawadhu' (humility) that are characteristic of Islamic boarding school culture.